Sport fishing in Brazil: the current state - Chiara Lubich; Flávia Siqueira-Souza; Carlos Freitas (Boletim do Instituto de Pesca)
Sport fishing has ecological, economic, and social importance, but there are few studies that characterize it according to the sustainability tripod. Due to this gap, we present a systematic review of the literature to evaluate the current situation of sport fishing in Brazil. The papers on the subject were systematically evaluated based on quantitative criteria. Additionally, in order to create a list of the species of interest of sport fishers, the survey of 22 papers was carried out regarding the species caught. A total of 70 complete papers published between 1994 and 2021 were included in the study. Since the 1990s, publications have increased quantitatively, with most studies coming from the South-Eastern region of Brazil (39.19%). The papers published discussed, in the majority, the sport fishing carried out in marine environment (55.38%), and the focus was “fishing and fishers” (30%). Evaluating the sustainability tripod, most of the papers provided only information regarding the ecological aspect (58.57%). About 330 species of marine and freshwater fish of interest to sport fishers were dealt with in the studies. This information reflects the current state of knowledge about Brazilian sport fishing, and it can serve as a basis for the management of the activity and the target species used by fishers. Additionally, the present review can serve as an aid for future research on this topic.